Cytokine screening identifies TNF to potentially enhance immunogenicity of pediatric sarcomas - Gassmann, Hendrik; Thiede, Melanie; Weiß, Jennifer; Biele, Emilie; Flohé, Luisa; Lachermaier, Helena; Prexler, Carolin; Evdokimova, Valentina; Radvanyi, Laszlo; Akhtar, Irfan; Morcos, Mina N. F.; Auer, Franziska; et al. (Frontiers in Immunology, 2024)
Pediatric sarcomas, including osteosarcoma (OS), Ewing sarcoma (EwS) and rhabdomyosarcoma (RMS) carry low somatic mutational burden and low expression of MHC-I expressionmolecules, posing a challenge for T cell therapies. Our previous study showed that mediators of monocyte maturation sensitized the EwS cell line A673 to lysis by HLA-A*02:01/CHM1 319 -specific allorestricted T cell receptor (TCR) transgenic CD8 + T cells (CHM1 319 CD8 + T cells). In this study, we tested a panel of monocyte maturation cytokines for their ability to upregulate immunogenic cell surface markers on OS, EwS and RMS cell lines. We observed that TNF and IL-1β upregulated MHC class I, ICAM-1 as well as CD83 and PD-L1 on the surface of pediatric sarcoma cell lines, while IL-4, GM-CSF, IL-6 and PGE2 failed to induce respective effects. Although pretreatment of pediatric sarcoma cell lines with TNF did not improve unspecific peripheral blood mononuclear cells (PBMCs) cytotoxicity, TNF enhanced specific recognition lysis of 1/3 HLA-A2 + EwS cell lines by CHM1 319 CD8 + T cells depending on MHC-I expression and ICAM-1 upregulation. Our study supports utilization of TNF or TNF-inducing regimens for upregulation of MHC-I and costimulatory surface molecules on pediatric sarcoma cells and for enhancing recognition of responsive HLA-A2-positive EwS tumor cells by antigen-specific CD8 + T cells.